Pengaruh budaya organisasi dan komitmen organisasi terhadap kinerja karyawan instalasi rawat inap medik rsup sanglah denpasar - Ni Nyoman Menuh; Ni Kadek Saraswastini (STIMI Handayani Denpasar, 2023)
The purpose of this study was to determine and analyze the influence of organizational culture and organizational commitment on employee performance at the Inpatient Medical Installation at Sanglah Hospital Denpasar. The types of data used in this study are qualitative data and quantitative data, with data sources namely primary data and secondary data. Methods of data collection is done by distributing questionnaires to respondents. The results showed that organizational culture had a positive and significant effect on employee performance, organizational commitment had a positive and significant effect on employee performance, organizational culture and organizational commitment simultaneously had a positive and significant effect on employee performance at the inpatient medical installation at Sanglah Hospital Denpasar.